1988
DOI: 10.1021/bi00411a039
|View full text |Cite
|
Sign up to set email alerts
|

Purification of a monocyte chemotactic factor secreted by nonhuman primate vascular cells in culture

Abstract: A protein chemotactic for peripheral blood monocytes (SMC-CF) of potential importance in their recruitment to the arterial intima in atherogenesis was purified from serum-free medium conditioned by cultured baboon aortic medial smooth muscle cells. The purification of SMC-CF was monitored by a filter assay using human peripheral blood mononuclear cells and was achieved by batch separation on a cation-exchange gel followed by gel permeation chromatography, ion-exchange high-performance liquid chromatography (HP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
141
0
2

Year Published

1989
1989
2006
2006

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 247 publications
(147 citation statements)
references
References 38 publications
4
141
0
2
Order By: Relevance
“…The amino acid composition of a monocyte chemoattractant produced by aortic smooth muscle cells of the baboon [27] is identical to that of MCP-1 [3]. Hybridization of the MCP-1 cDNA probe with baboon DNA ( fig.6) is added evidence for the relationship between MCP-1 and the smooth muscle product, and indicates that both lymphocytes and vascular smooth muscle cells can produce this attractant.…”
Section: Discussionmentioning
confidence: 99%
“…The amino acid composition of a monocyte chemoattractant produced by aortic smooth muscle cells of the baboon [27] is identical to that of MCP-1 [3]. Hybridization of the MCP-1 cDNA probe with baboon DNA ( fig.6) is added evidence for the relationship between MCP-1 and the smooth muscle product, and indicates that both lymphocytes and vascular smooth muscle cells can produce this attractant.…”
Section: Discussionmentioning
confidence: 99%
“…Chemokine receptor 2 is the receptor for monocyte chemoattractant proteins (MCPs) 3 [1][2][3][4][5]. The MCPs are potent chemoattractants for monocytes (7)(8)(9), memory T cells (10), NK cells (11,12), and immature dendritic cells (DCs) (13). We and others have shown that deletion of CCR2 reduces the number of macrophages recruited into the peritoneum after thioglycolate administration (14 -16), consistent with the possibility that CCR2 is normally present on murine monocytes/macrophages.…”
mentioning
confidence: 84%
“…Measurement of lymphomonocyte chemotaxis was performed by using 5 µm filters and modified Boyden chambers, as described by Valente et al 23 The cell preparation (200 µL) was placed above the filters, and the chambers were incubated at 37°C for 90 minutes. After staining with Giemsa, cells migrating to the underside of the filters were quantitated as the mean number of cells in 10 high power fields.…”
Section: Methodsmentioning
confidence: 99%